Hydrogen production via a two-step water splitting thermochemical cycle based on metal oxide – A review. (1st June 2020) - Mao, Yanpeng; Gao, Yibo; Dong, Wei; Wu, Han; Song, Zhanlong; Zhao, Xiqiang; Sun, Jing; Wang, Wenlong
Highlights: Advances in hydrogen production via two-step water-splitting thermochemical cycles were critically reviewed. The cycle characteristics were compared based on metal oxide redox pairs. Heat sources and chemical reactors development for cyclic reactions were evaluated circumstantially. Abstract: Hydrogen production via a two-step thermochemical cycle has attracted considerable research interest as it can directly utilize the heat of the high temperature reactor, which eliminates the need for power generation steps and increases energy efficiency, and is understood to be a promising method for producing hydrogen on an industrial scale. The thermochemical cycle uses a metal oxide as a catalyst and involves two steps: thermal reduction and water splitting. The cycle process only requires the input of heat and water to continuously regenerate hydrogen and oxygen, which has almost no impact on the environment and has the potential for sustainable development. Herein we reviewed the two-step thermochemical cycle with regard to reaction heat source, metal oxide characteristics, and chemical reactors. The performance of volatile and non-volatile metal oxides in the cycle reactions has been thoroughly investigated. To date, the most widely studied metal oxides are ZnO/Zn, SnO2 /SnO, ceria-based oxides, and iron-based oxides. Among them, doped-ceria and iron-based oxides, which have high redox activities and cycle stabilities, are considered to be the most promising materials. The possibility of achieving large-scale industrial production and the perspective on future material development were also analyzed. It was proved that the poly-cation oxides (PCOs) studied have great potential for hydrolysis, and the use of oxygen transport membrane reactor provides a new perspective for solar hydrogen production.